Training Specificity and Ecological Validity: Challenging Reductionist Exercise Paradigms for Older Adults - Morrison, Robert T (Open Science Journal, 2024)
This article challenges the prevalent approach in exercise science for improving functional performance in older adults. It argues that contemporary exercise research and practice adheres to an outdated paradigm based on the motor schema theory. This approach diminishes the principle of specificity in training and assessments. The author supports this central critique through fundamental principles, including conceptual imprecision, paradigmatic limitations, and the tenets of motor learning. Additional evidence from exercise science literature demonstrates that these issues undermine the specificity principle. To address these shortcomings, the author proposes a preliminary framework called ‘The Emergence of Skilled Mobility in Ageing (ESMA)’, which aligns training and evaluation with individual-task-environment constraints. This framework recognises the critical role of adaptive variability and representative practice design for optimising coordination, skills, and mobility. The proposed framework has significant implications for interdisciplinary collaboration and knowledge translation, through focused and ecologically valid assessments and interventions. Overall, this article identifies key gaps in the current exercise science paradigm and offers an integrated solution that focuses on specificity and real-world functioning.